Comparison on evolution of volatile compounds and aroma attributes in different pH-adjusted fermented bog bilberry syrup wines during bottle-aging period. (April 2018) - Wang, Shaoyang; Li, Yiqing; Ren, Jie; Gu, Pan; Li, Teng; Wu, Yuwen; Zhang, Bolin; Zhu, Baoqing
Abstract: Bottle-aging improves the overall aroma of wine and different pH fermentation conditions can alter the evolution pattern of volatiles in wine during bottle-aging. In this study, the evolution of volatiles and aromas was investigated in different pH fermented bog bilberry syrup wines during a 6-month bottle-aging. Results showed that a total of 93 volatile compounds were found in bog bilberry syrup wine after fermentation. During bottle-aging, these volatiles exhibited 8 evolution patterns, and pH adjustment affected the evolution of esters, higher alcohols and acids. Eleven volatiles contributed their flavor scents to bog bilberry syrup wine overall aroma. Fruity, fatty and solvent scents were the major aromas, and pH adjustment induced an alteration on the aroma attributes during bottle-aging. Principal component analysis indicated that bottle-aging process segregated the sensory similarity of bog bilberry syrup wines through altering their aroma attributes. Low pH wine was separated from middle and high pH wines after 6 months of bottle-aging due to its high level of solvent and balsamic aromas. This indicated that pH adjustment resulted in a pattern difference on the evolution of volatiles during bottle-aging, which altered aroma profile of bog bilberry syrup wine.